STATE OF RELIGION IN A GLOBALIZED WORLD - Bombongan Jr, Dominador (Journal of Dharma, 2009)
Our globalized world is saddled with deepening poverty, environmental destruction and social disintegration. In the face of this multifaceted global crisis, has religion anything worthwhile to offer? Put differently, what constitutes an appropriate religious response to globalization? Samuel Huntington has already pointed out that our future will be characterized by a clash of civilizations which is stamped by religions, i.e., Islamic or Confucian-Asian civilizations versus the West. We may not however, agree with such a gloomy depiction of the future. The encounter among civilizations can be an opportunity for dialogue and cooperation.1 By citing Huntington, we want to raise here the question of the perceived significance of religion for the future. Religion will play a crucial role in the future. This is contrary to the belief that religion has died out in the process of secularization. It is, in fact, a recalcitrant phenomenon which refuses to go away.2 Religion has come back, in our globalized world, although perhaps not so much in its institutionalized version. This article will further reflect on the significance of religions in our globalized world by drawing on the works of two respected sociologists of religion namely, Roland Robertson and Peter Beyer. I will commence with a brief description of the multifaceted reality of the globalization process and the challenges it poses for religions, after which I will discuss the ideas of the two above mentioned authors.